2012
DOI: 10.1111/j.1365-2036.2012.05103.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of the oesophageal balloon distension test in the evaluation of oesophageal chest pain

Abstract: SUMMARY Background Oesophageal balloon distension test (EBDT) has been advocated for the evaluation of functional oesophageal noncardiac chest pain (NCCP), but its diagnostic utility remains unclear. Aim To prospectively assess the diagnostic yield of EBDT in clinical practice and compare its yield with standard oesophageal tests. Methods Over a period of 6 years, patients with chest pain and negative cardiac work-up underwent sequential testing with endoscopy/biopsy, oesophageal manometry, 24 h pH study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…In FD, large-scale studies have demonstrated an association with pain predominance,7 18 and in patients with non-cardiac chest pain, oesophageal hypersensitivity can be found in approximately a third of the patients 19. In IBS, an association with the overall severity of IBS symptoms have been found in several large studies,15 16 21 34 and among the individual IBS symptoms the most consistent associations have been demonstrated with pain and bloating 16 34.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In FD, large-scale studies have demonstrated an association with pain predominance,7 18 and in patients with non-cardiac chest pain, oesophageal hypersensitivity can be found in approximately a third of the patients 19. In IBS, an association with the overall severity of IBS symptoms have been found in several large studies,15 16 21 34 and among the individual IBS symptoms the most consistent associations have been demonstrated with pain and bloating 16 34.…”
Section: Discussionmentioning
confidence: 92%
“…To obtain comparable scales for the overall GI symptom severity in all five cohorts, z scores were calculated and used when displaying the results for GI (IBS and dyspepsia) severity. Based on information from the literature with a third of patients on average demonstrating visceral hypersensitivity in FGIDs,7 8 19 21 the subjects in the five cohorts were divided into sensitivity tertiles based on their pain (IBS studies) or discomfort thresholds (FD cohort). GI symptom severity was compared between these sensitivity tertile groups using one-way analysis of variance (ANOVA) with post hoc pairwise comparisons between all three groups using independent samples t-tests with Bonferroni correction for multiple testing, as well as one-way between-groups ANOVA with linear contrast analyses to analyse the presence of a linear trend.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…70 When esophageal balloon distension test was performed after excluding GERD and achalasia from 332 NCCP patients, hypersensitivity was found in 71% (128/181) of the remaining patients. 21 When esophageal motility disorders other than achalasia were also ex- In a recent systematic review of published trials regarding effects of antidepressants on non-GERD−related NCCP, 74 6…”
Section: ) Esophageal Visceral Hypersensitivitymentioning
confidence: 99%